Evolution of milk oligosaccharides: Origin and selectivity of the ratio of milk oligosaccharides to lactose among mammals - Urashima, Tadasu; Katayama, Takane; Sakanaka, Mikiyasu; Fukuda, Kenji; Messer, Michael (Biochimica et biophysica acta. General subjects, 2022)
The carbohydrate fraction of mammalian milk is constituted of lactose and oligosaccharides, most of which contain a lactose unit at their reducing ends. Although lactose is the predominant saccharide in the milk of most eutherians, oligosaccharides significantly predominate over lactose in the milk of monotremes and marsupials. This review describes the most likely process by which lactose and milk oligosaccharides were acquired during the evolution of mammals and the mechanisms by which these saccharides are digested and absorbed by the suckling neonates. During the evolution of mammals, c-type lysozyme evolved to α-lactalbumin. This permitted the biosynthesis of lactose by modulating the substrate specificity of β4galactosyltransferase 1, thus enabling the concomitant biosynthesis of milk oligosaccharides through the activities of several glycosyltransferases using lactose as an acceptor. In most eutherian mammals the digestion of lactose to glucose and galactose is achieved through the action of intestinal lactase (β-galactosidase), which is located within the small intestinal brush border. This enzyme, however, is absent in neonatal monotremes and macropod marsupials. It has therefore been proposed that in these species the absorption of milk oligosaccharides is achieved by pinocytosis or endocytosis, after which digestion occurs through the actions of several lysosomal acid glycosidases. This process would enable the milk oligosaccharides of monotremes and marsupials to be utilized as a significant energy source for the suckling neonates. The evolution and significance of milk oligosaccharides is discussed in relation to the evolution of mammals. •Although Mammalian milk usually contain lactose as the predominant saccharide, the milk oligosaccharides predominate over lactose in the milks of monotremes, marsupials and most caniformia species among carnivora within eutherians.•It is hypothesized that the acquisition of milk oligosaccharides as well as of lactose had been triggered by molecular evolution of α-lactalbumin, a milk protein, from lysozyme.•In the suckling neonates of most euthrian species lactose is split into glucose and galactose by intestinal lactase which is located in the membrane of the microvilli of the small intestinal brush border, and the monosaccarides are transported into the enterocytes via specific mechanisms to be utilized as the significant energy source.•In the suckling neonates of monotremes and marsupials the milk oligosaccharides enter the small intestinal cells via pinocytosis or endocytosis and are transferred to lysosomes in which they are hydrolyzed to monosaccharides by several acid glycosidases.•In human breastfed infants a major part of milk oligosaccharides is not hydrolyzed and absorbed in small intestine to reach the colon, but functions as prebiotics to stimulate the beneficial colonic bacteria, anti infection factor against pathogenic bacteria or viruses, immune modulation factor, nerve developing factor, and colonic barrier function strengthening factor.